Pengaruh Islamic Branding dan Display Store terhadap Keputusan Pembelian Busana Muslim di Toko Mahabatullah Jambi - Marsela, Fahira; Hafiz, Ahsan Putra; Fikri, Attar Satria (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the influence of Islamic branding and store displays on purchasing decisions for Muslim clothing at the Mahabatullah Jambi Store. The population used in this research were consumers who had purchased Muslim fashion products at the Mahabatullah Jambi Store. The research method used was quantitative with a sample size of 67 respondents. The data analysis methods used are data collection, data presentation, and drawing conclusions. The results of this research show that simultaneously and partially there is a positive and significant influence between Islamic branding and store displays on the decision to purchase Muslim clothing at the Mahabatullah Jambi Store.